Penggunaan Aplikasi Whatsapp Dalam Pembelajaran Seni Tari Di SMA N 12 Padang - Bunga Naselia; Indrayuda Indrayuda (SENDRATASIK UNP, 2021)
This This article aims to describe the use of the Whatsapp application in the industrial era 4.0 in learning dance at SMA N 12 Padang. This research is a qualitative research using descriptive method. The object of research is the use of the Whatsapp application in the industrial era 4.0 in class X IPA 2 SMA Negeri 12 Padang in learning the art of dance with KD material 3.1 Understanding concepts, techniques, and procedures in a variety of traditional dance movements. and KD 4.1 Demonstrating dance moves based on concepts, techniques , and the procedure according to the count/beat. The researcher acts as the main instrument in this research, and is assisted by a recording device, and audio, visual and audio visual matching tools. Data was collected through direct observation, interviews, and documentation, as well as literature study. The data were analyzed through the procedure referred to by Sugiyono, namely finding information related to the use of the Whatsapp application in dance learning, then grouping the information found and describing the information systematically and structured about the use of the Whatsapp application in dance learning including teaching preparation, delivery of material, assignment, training/ practice and evaluation. In the next stage, the data is selected and the results of the selection are verified and concluded by the researcher. The findings from the results of the study concluded that the implementation of traditional dance movement learning has three stages including, pre-learning activities, core activities, and closing activities. Second, the obstacles to using the Whatsapp application in learning traditional dance movements include that it is difficult for teachers to monitor and know the abilities of students in learning traditional dance movements and students find it difficult to learn traditional forms of movement independently. Third, some of the advantages and disadvantages of using the Whatsapp application in the learning process of various dance moves include, different signal strengths, and smartphone memory being full due to learning material files causing slow smartphones.